2015
DOI: 10.1002/2014wr016689
|View full text |Cite
|
Sign up to set email alerts
|

Impact of degrading permafrost on subsurface solute transport pathways and travel times

Abstract: Subsurface solute transport under surface warming and degrading permafrost conditions is studied using a physically based model of coupled cryotic and hydrogeological flow processes combined with a particle tracking method. Changes in the subsurface water and inert solute pathways and travel times are analyzed for different modeled geological configurations. For all simulated cases, the minimum and mean travel times increase nonlinearly with warming irrespective of geological configuration and heterogeneity st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 68 publications
3
40
0
Order By: Relevance
“…The thickness of the layer of ground above permafrost (i.e. supra-permafrost layer) is expected to continue increasing as a result of warming (Lawrence et al, 2012;Frampton and Destouni, 2015), catalyzing the transition to thermokarst landscapes (Kokelj and Jorgenson, 2013). The supra-permafrost layer includes the active layer, which freezes and thaws annually, but may also include a perennially-unfrozen layer (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The thickness of the layer of ground above permafrost (i.e. supra-permafrost layer) is expected to continue increasing as a result of warming (Lawrence et al, 2012;Frampton and Destouni, 2015), catalyzing the transition to thermokarst landscapes (Kokelj and Jorgenson, 2013). The supra-permafrost layer includes the active layer, which freezes and thaws annually, but may also include a perennially-unfrozen layer (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Many authors have reported that decreases in the extent of permafrost and associated increases of the active layer thickness in a catchment are marked by a decrease in DOC concentrations and an increase in solute concentrations in stream water. This seems to indicate deeper groundwater flow paths with longer residence and weathering times . However, Raudina et al nuance these observations.…”
Section: Impacts Of Climate Change On Groundwater Quality In Permafromentioning
confidence: 97%
“…The principal impacts of climate change on groundwater quality in permafrost regions will therefore be linked primarily to the reduction or loss of the confining layer, including impacts such as deepening suprapermafrost groundwater flow paths, increased rock–water interactions, more direct groundwater–surface water interactions and increased groundwater vulnerability to contamination …”
Section: Impacts Of Climate Change On Groundwater Quality In Permafromentioning
confidence: 99%
“…Part of these impacts are directly linked to changes in the hydrological conditions (Bense et al, 2009) with profound changes in the permafrost hydrology, active soil moisture distribution and flow patterns 20 (Bring et al, 2016). The deepening of the active layer will change the flow and transport pattern and typically lead to longer travel paths and times (Frey and McClelland, 2009;Frampton and Destouni, 2015). An ecological effect is related to the release and subsequent migration of inorganic nitrogen stored in the perennially frozen ground (Elberling et al, 2010) or from winter decomposition (Blok et al, 2016).…”
Section: Introductionmentioning
confidence: 99%